Konflik Indonesia-Jepang Di Dalam Pasar Otomotif: Penerapan Analytic Hierarchy Process (Ahp) Dan Game Theory - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT This study stipulates the conflict between Indonesia and Japan due to serious allegations of the National Car program that is seemingly to protect Indonesian-domestic automotive market. Being aware of potential new conflicts and assuming the program is still upheld, the nature and intensity of the conflict are described quantitatively by applying the Analytic Hierarchy Process (AN?) in a non-zero sum game framework. The AHP is used to find relative importance of strategies that are possible to be implemented by Indonesia and Japan and to measure their payoffs.